2015
DOI: 10.1038/srep16078
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of oral goshajinkigan on chronic oxaliplatin-induced hypoesthesia in rats

Abstract: Oxaliplatin, a widely used chemotherapeutic agent, induces peripheral neuropathy that manifests itself as two distinct phases: acute cold hyperesthesia and chronic peripheral hypoesthesia/dysesthesia. The latter is a serious dose-limiting side effect that can often lead to withdrawal of treatment. We have developed a rat model expressing both phases and used the model to investigate the action of goshajinkigan (GJG), a traditional Japanese herbal medicine, which was reported to ameliorate oxaliplatin-induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…One such pharmacological herbal mixture, GJG, has been shown in animal studies and small clinical studies to prevent CIPN [Schroder, et al 2013, Tawata, et al 1994]. GJG alleviates paclitaxel induced hyperalgesia by preventing degeneration of the ganglion cells and suppressing TRPV4 expression [Matsumura, et al 2014], bortezomib-induced mechanical allodynia through the kappa opioid receptor [Higuchi, et al 2015] and oxaliplatin through attenuation of the generation of oxaliplatin-induced reactive oxygen species [Kono, et al 2015]. Our research has demonstrated the potentiality of GJG to protect human iPSC-derived cortical neurons against paclitaxel-induced neuropathy without causing decreased sensitivity of particular cancer cells (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One such pharmacological herbal mixture, GJG, has been shown in animal studies and small clinical studies to prevent CIPN [Schroder, et al 2013, Tawata, et al 1994]. GJG alleviates paclitaxel induced hyperalgesia by preventing degeneration of the ganglion cells and suppressing TRPV4 expression [Matsumura, et al 2014], bortezomib-induced mechanical allodynia through the kappa opioid receptor [Higuchi, et al 2015] and oxaliplatin through attenuation of the generation of oxaliplatin-induced reactive oxygen species [Kono, et al 2015]. Our research has demonstrated the potentiality of GJG to protect human iPSC-derived cortical neurons against paclitaxel-induced neuropathy without causing decreased sensitivity of particular cancer cells (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Kono et al examined a preventive effect of Jesengsingi-Hwan on chronic oxaliplatin-induced hypoesthesia in rats. Oral administration of Jesengsingi-Hwan (0.3 or 1.0 g/kg, 5 times a week for 8 weeks) ameliorated abnormal sensations and histological damage to the sciatic nerve [42]. In a retrospective clinical study, Kono et al examined the benefits of Jesengsingi-Hwan on oxaliplatin treatment involved in peripheral neuropathy.…”
Section: Jesengsingi-hwan (Goshajinkigan In Japanese)mentioning
confidence: 99%
“…Reduces peripheral neuropathy without influence on anti-cancer potency Ameliorates abnormal sensations and histological damage to the sciatic nerve [41,42] Paclitaxel in mice Inhibits mechanical allodynia [43] Oxaliplatin in a placebo-controlled double-blind randomized study Delays onset of grade 2 or greater peripheral neurotoxicity without impairing FOLFOX efficacy with an acceptable safety margin [44,45] Prevents exacerbation of peripheral neuropathy [46,47] A clinical trial enrolling 82 patients Reduces peripheral neuropathy [48] …”
Section: Oxaliplatin In Ratsmentioning
confidence: 99%
“…2C-F). In addition, Kono et al reported a morphological analysis demonstrated that oxaliplatin causes the atrophy of axons containing myelinated nerve fibers but not non-myelinated nerve fibers in the sciatic nerves in rats and that this effect was ameliorated by GJG 17 . The simplest interpretation of these findings is that an increase in the sensitivity of either Aδ- or Aβ-fibers or both is involved in the induction of mechanical allodynia and that GJG, acting on these sensory fibers, inhibits their sensitization.…”
Section: Discussionmentioning
confidence: 99%